STUDI FASIES, BATIMETRI, LINGKUNGAN PENGENDAPAN, DAN SIKUENSTRATIGRAFI SUMUR ALAF#1 DAN SUMUR ALAF#154 LAPANGAN WSDA CEKUNGAN SUMATERA TENGAH BERDASARKAN DATA INTI BATUAN, LOG GAMMA RAY DAN BIOSTRATIGRAFI - Nela Paramitha Rattyananda (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
The research area is located on the WSDA Field which is part of the Central Sumatra Basin and is composed of Tertiary sediments. Well Alaf#1 and Well Alaf#154 are two wells located on Field WSDA. In the sediments of the study area was found Sihapas Group (Bekasap Formation and Telisa Formation) which has a relatively abundant microfossils. Both of these formations are formed in the phase where there is a transgression that can be applied to the stratigraphy sequence analysis.This study has the objective to determine the depositional facies rocks based on the core data and the Gamma Ray log data, determine zoning, paleobathymetry, depositional environment based identification lithofacies, elektrofacies and biostratigraphy, and depositional dynamics stratigraphy sequence determine Alaf Well Alaf#1 and Well Alaf#154 WSDA Field of Central Sumatra Basin.The method used in this research is descriptive and analytical methods. Descriptive methods include case studies and literature. Analysis methods include deposition facies analysis, micropaleontology analysis and stratigraphy sequence analysis using rock core data, the data Log Gamma Ray and data biostratigraphy Well Alaf#1 and Well Alaf#154. From log data and core rock the data can be identified depositional facies. Then the elektrofacies data and litofacies the approach core to log and trace fossil analysis will be obtained depositional environment. Biostratigraphic data is used to determine zoning and paleobathymetry. Determination of the depositional dynamics stratigraphy sequence determine Alaf Well Alaf#1 and Well Alaf#154 obtained by pulling the stratigraphic marker based on microfossil data, calcareous nannoplankton, log pattern analysis and depositional facies analysis.Based on the litofacies, elektrofacies and biostratigraphy analysis, Well Alaf#1 and Well Alaf#154 have a range of Early Miocene age relative to the bathymetric range Litoral – Middle Neritic and have a tide dominated delta depositional environment. Results showed stratigraphy sequence interpretation cycle of sequence marked by a boundary looping are SB (Sequence Boundary) and MFS (Maximum Flooding Surface). Well Alaf#1 has 3 cycles sequence and Well Alaf#154 has 4 cycles sikuen. On the correlation stratigraphy sequence of Well Alaf#1 and Well Alaf#154, there are two cycles sequence, but only one complete cycle consisting sequence of SB2, HST (Highstand System Tract), MFS3, TST (Transgresive System Tract) then SB3. This is due to limit the scope of the study in the study area does not include all parts of the looping process that occurs in the study area.